Tribo-mechanical behaviour of aluminium alloy (AlSi10Mg) reinforced with palmyra shell ash and silicon carbide particles - Subramaniam, Shankar; Raju, Naveenkumar; Shanmugam, Elango; Rajavel, Nithyaprakash; Pramanik, Alokesh; Basak, Animesh Kumar; Gur, Ali Kaya (Edp Sciences S A, 2022)
AlSi10Mg alloy is blended with palmyra shell ash (PSA) and silicon carbide (SiC) using stir casting route and its tribological properties on the reinforcement addition with the aluminium alloy (AlSi10Mg) hybrid composite are studied. Hybrid composites are fabricated by adding 3, 6 and 9 wt.% of silicon carbide and 9 wt.% palmyra shell ash particle into aluminium (AlSi10Mg) alloy. The dry sliding properties of the AlSi10Mg hybrid alloy composite were examined under different loading conditions against carbon steel disc using a pin-on-disc Tribometer. The results showed that the hybrid metal matrix composite reinforced with silicon carbide and palmyra shell had better tribological characteristics than the composite reinforced with single reinforcement (palmyra shell ash). Increase in wt.% of reinforcement increases the hardness as well as the tensile strength of the composites. Morphological analysis resulted that the abrasive wear mechanism was dominant and causes high wear evolution in dry sliding condition.
Keywords: aluminium alloy; palmyra shell ash; dry sliding; silicon carbide; wear